Infection Complications in Hematopoietic Stem Cells Transplant Recipients: Do Genetics Really Matter? - Espinoza, J. Luis; Wadasaki, Yohei; Takami, Akiyoshi (Frontiers in Microbiology, 2018)
Hematopoietic stem cell transplantation (HSCT) is a highly advanced technique that offers a potential cure for an increasing number of life-threatening diseases. Enormous progress achieved in the last decade, including the refinement of donor selection and advancements in patient supportive care, had significantly improved transplant outcomes; however, invasive infections, graft-versus-host disease (GVHD) and other serious complications still represent a major source of morbidity and mortality in HSCT recipients. The damage of anatomical barriers due to pre-transplant conditioning, a severely damaged immune function and a profound disruption in the composition of gut microbial commensals (gut microbiota) are alterations inherent to the transplant procedure that are directly implicated in the development of invasive infections and other HSCT complications. Although HLA-matching represents the most important genetic predictor of transplant outcomes, genetic variants in non-HLA genes, especially single nucleotide polymorphisms (SNPs) of genes encoding proteins associated with the immune response to tissue injury and pathogen infection have also been proposed as additional risk factors implicated in the occurrence of HSCT complications. Furthermore, although the microbiota composition is affected by several factors, recent evidence suggests that certain host genetic variants are associated with an altered composition of the gut microbiome and may, therefore, predispose some individuals to invasive infectious complications. This article summarizes the current understanding of the influence that genetic variants in non-HLA genes have on the development of infectious complications in HSCT recipients.